Early or Late Bacterial Lung Infection Increases Mortality After Traumatic Brain Injury in Male Mice and Chronically Impairs Monocyte Innate Immune Function - Doran, Sarah J; Henry, Rebecca J; Shirey, Kari Ann; Barrett, James P; Ritzel, Rodney M; Lai, Wendy; Blanco, Jorge C; Faden, Alan I; Vogel, Stefanie N; Loane, David J (Critical care medicine, 2020)
Respiratory infections in the postacute phase of traumatic brain injury impede optimal recovery and contribute substantially to overall morbidity and mortality. This study investigated bidirectional innate immune responses between the injured brain and lung, using a controlled cortical impact model followed by secondary Streptococcus pneumoniae infection in mice. Experimental study. Research laboratory. Adult male C57BL/6J mice. C57BL/6J mice were subjected to sham surgery or moderate-level controlled cortical impact and infected intranasally with S. pneumoniae (1,500 colony-forming units) or vehicle (phosphate-buffered saline) at 3 or 60 days post-injury. At 3 days post-injury, S. pneumoniae-infected traumatic brain injury mice (TBI + Sp) had a 25% mortality rate, in contrast to no mortality in S. pneumoniae-infected sham (Sham + Sp) animals. TBI + Sp mice infected 60 days post-injury had a 60% mortality compared with 5% mortality in Sham + Sp mice. In both studies, TBI + Sp mice had poorer motor function recovery compared with TBI + PBS mice. There was increased expression of pro-inflammatory markers in cortex of TBI + Sp compared with TBI + PBS mice after both early and late infection, indicating enhanced post-traumatic neuroinflammation. In addition, monocytes from lungs of TBI + Sp mice were immunosuppressed acutely after traumatic brain injury and could not produce interleukin-1β, tumor necrosis factor-α, or reactive oxygen species. In contrast, after delayed infection monocytes from TBI + Sp mice had higher levels of interleukin-1β, tumor necrosis factor-α, and reactive oxygen species when compared with Sham + Sp mice. Increased bacterial burden and pathology was also found in lungs of TBI + Sp mice. Traumatic brain injury causes monocyte functional impairments that may affect the host's susceptibility to respiratory infections. Chronically injured mice had greater mortality following S. pneumoniae infection, which suggests that respiratory infections even late after traumatic brain injury may pose a more serious threat than is currently appreciated.